Leveling as an Educational Theory for Renewable Energy Careers (Docentes 2.0 Journal, 2020)
Physics is a science that provides the basic knowledge that is necessary to carry out studies on renewable energy. Having a deficit in this matter is a general problem in students who enter the university level in order to study said career. It could be verified through diagnostic tests that 57% have difficulty with the concept of energy, its types, forms and transformations. For this reason, the objective sought with this work was a didactic proposal that consists of a leveling course that was applied to 24 students at the Popular University of Chontalpa, who form a first-year pilot group, first semester in this career. This course was applied in the first semester of this career. A mixed research method was used that represented a set of systematic, empirical and critical research processes, which involve the collection of both quantitative and qualitative data. It was carried out through action research and a case study based on Stake's proposal (2005). As a result, significant advances were observed in the interpretation of the concept of energy, its conservation, exemplifying renewable sources and explanations about the relationships between these forms, while difficulties were presented in the conversions of physical units. The didactic proposal contributed to improve the deficiencies in the students and their performance; participating and doing activities during classes. It was demonstrated that it is necessary to link theoretical elements with daily life and collaborative and individual work.
Keywords: Didactic proposal; leveling course; renewable energy; learning strategies